Altered morphokinetics in equine embryos from oocytes exposed to DEHP during IVM. Issue 10 (25th April 2019) - Marzano, Giuseppina; Mastrorocco, Antonella; Zianni, Rosalia; Mangiacotti, Michele; Chiaravalle, Antonio E.; Lacalandra, Giovanni M.; Minervini, Fiorenza; Cardinali, Angela; Macciocca, Maria; Vicenti, Rossella; Fabbri, Raffaella; Hinrichs, Katrin; et al.
Abstract: Di‐(2‐ethylhexyl) phthalate (DEHP) is a commonly used plasticizer with endocrine‐disrupting properties. In this study, we used an equine model to investigate DEHP concentrations in ovarian follicular fluid (FF), and to determine the effects of exposure of oocytes to potentially toxic concentrations of DEHP during in vitro maturation (IVM) on embryo development and quality. Embryo development was evaluated using time‐lapse monitoring (TLM), a photomicroscopic tool that reveals abnormalities in cleavage kinetics unobservable by conventional morphology assessment. Blastocyst bioenergetic/oxidative status was assessed by confocal analysis. The possibility that verbascoside (VB), a bioactive polyphenol with antioxidant activity, could counteract DEHP‐induced oocyte oxidative damage, was investigated. DEHP was detected in FF and in IVM media at concentrations up to 60 nM. Culture of oocytes in the presence of 500 nM DEHP delayed second polar body extrusion, reduced duration of the second cell cycle, and increased the percentage of embryos showing abrupt multiple cleavage, compared with controls. Mitochondrial activity and intracellular levels of reactive oxygen species were reduced in blastocysts from DEHP‐exposed oocytes. VB addition during IVM limited DEHP‐induced blastocyst damage. In conclusion, DEHP is detectable in equine FF and culture medium, and oocyte exposure to increased concentrations of DEHP during IVM affects preimplantation embryo development. Moreover, TLM, reported for the first time in the horse in this study, is an efficient tool for identifying altered morphokinetic parameters and cleavage abnormalities associated with exposure to toxic compounds. Abstract : 1. Di‐(2‐ethylhexyl) phthalate (DEHP) is detected at nanomolar concentrations in equine follicular fluid. 1. Exposure of equine oocytes to DEHP during in vitro maturation affects early and late stage preimplantation development. 1. The use of time‐lapse monitoring in reproductive toxicology is recommended to better define the effects of toxic compounds.